Single-Walled Carbon Nanotube Dominated Micron-Wide Stripe Patterned-Based Ferroelectric Field-Effect Transistors with HfO2 Defect Control Layer - Qiuhong Tan (Nanoscale Research Letters, 2018)
Abstract Ferroelectric field-effect transistors (FeFETs) with single-walled carbon nanotube (SWCNT) dominated micron-wide stripe patterned as channel, (Bi,Nd)4Ti3O12 films as insulator, and HfO2 films as defect control layer were developed and fabricated. The prepared SWCNT-FeFETs possess excellent properties such as large channel conductance, high on/off current ratio, high channel carrier mobility, great fatigue endurance performance, and data retention. Despite its thin capacitance equivalent thickness, the gate insulator with HfO2 defect control layer shows a low leakage current density of 3.1 × 10−9 A/cm2 at a gate voltage of − 3 V.